نجاح رسول داخل دراسة احصائيه لجودة خدمات الهاتف النقال في مركز محافظة ذي قار - نجاح رسول (University of Thi-Qar Journal of Science, 2019)
This study talking about the contentment of costumers of mobile service which supplied by  Zain, Asia cell and Furat phone companies in Thi-Qar governorate . We found that 37% from the sample of costumers are uncontent about the prices of callings ,about 32% considers the level of service is medium in Asia about 42% ,Zain about 28% and in Furat phone is about 40%.This reflected on the level of gratitude ( gratitude to the mark) where 26% of costumers don’t like change the Zain company , and about 37% to Asia cell and about 8% don’t like change Furat phone.According to this study, to reach the high level, must improve the prices to 81% , the competitive privileges about 6% , the level of net coverage about 52% and at last, variety of the offers and the services about 51% .